Ultrathin Oxide Passivation Layer by Rapid Thermal Oxidation for the Silicon Heterojunction Solar Cell Applications - Youngseok Lee; Woongkyo Oh; Vinh Ai Dao; Shahzada Qamar Hussain; Junsin Yi (International Journal of Photoenergy)
It is difficult to deposit extremely thin a-Si:H layer in heterojunction with intrinsic thin layer (HIT) solar cell due to thermal damage and tough process control. This study aims to understand oxide passivation mechanism of silicon surface using rapid thermal oxidation (RTO) process by examining surface effective lifetime and surface recombination velocity. The presence of thin insulating a-Si:H layer is the key to get high Voc by lowering the leakage current (I0) which improves the efficiency of HIT solar cell. The ultrathin thermal passivation silicon oxide (SiO2) layer was deposited by RTO system in the temperature range 500–950°C for 2 to 6 minutes. The thickness of the silicon oxide layer was affected by RTO annealing temperature and treatment time. The best value of surface recombination velocity was recorded for the sample treated at a temperature of 850°C for 6 minutes at O2 flow rate of 3 Lpm. A surface recombination velocity below 25 cm/s was obtained for the silicon oxide layer of 4 nm thickness. This ultrathin SiO2 layer was employed for the fabrication of HIT solar cell structure instead of a-Si:H, (i) layer and the passivation and tunneling effects of the silicon oxide layer were exploited. The photocurrent was decreased with the increase of illumination intensity and SiO2 thickness.